Implikasi Putusan Mahkamah Konstitusi Nomor 50/PUU-VI/2008 Terhadap Kebebasan Berekspresi di Sulawesi Selatan - Cheryn Ceria Desta A; Andi Nurulizzah Putri; Rerindita Sekar Seruni; Ahmad Reyhand Adriansyah Dwi Putra; Andi Batari Syiffa B. Asapa (Lembaga Intelektual Muda Maluku, 2026)
This research aims to analyze the implications of Constitutional Court Decision No. 50/PUU-VI/2008 on freedom of expression, particularly in its implementation in South Sulawesi. The research method used is normative legal research with statutory, case, and conceptual approaches to the Constitutional Court decision, relevant legislation, and law enforcement practices in the region. The findings show that the Constitutional Court decision has provided important normative clarification regarding the limits of freedom of expression within a democratic rule of law state. However, its implementation in South Sulawesi remains suboptimal, as indicated by approximately 37 alleged cases of restrictions on freedom of expression during the 2020–2024 period, with 62 percent of these cases processed under the Electronic Information and Transactions Law and defamation provisions. This condition reflects a gap between constitutional norms and law enforcement practices in the field. This study concludes that although Constitutional Court Decision No. 50/PUU-VI/2008 has strong normative authority in guaranteeing freedom of expression, its implementation effectiveness still faces challenges at the regional level. Strengthening legal understanding among law enforcement officials and harmonizing legal interpretation are necessary to ensure consistent protection of constitutional rights.